Struktur Tahan Gempa terhadap Ketidakberaturan Horizontal dan Vertikal Gedung Pendidikan Terpadu Agribisnis Politeknik Negeri Jember - Usman, Marzuqi; Sudarso, Sudarso; Ikhwanuddin, Ikhwanuddin (Universitas Batanghari Jambi, 2025)
Indonesia, located at the meeting point of three active pelates, is an earthquake-prone country, including Jember Regency which is close to the source of the Indo-Australian Pelate subduction earthquake. This condition requires building planning that is able to withstand earthquake loads in accordance with applicable earthquake resistance standards. One method used to weaken the resistance of structures to earthquakes is pushover analysis, which aims to determine the maximum force, freezing, and collapse patterns in structures due to earthquake loads. This study focuses on analyzing the irregularities of the horizontal and vertical structures of the Integrated Agribusiness Education Building of the Jember State Polytechnic using SAP2000 v22 software, which refers to the provisions of SNI 1726: 2019. The method used is quantitative analysis to transmit the performance of earthquake-resistant building structures. SAP2000 allows statistical, dynamic, linear, and nonlinear analysis to ensure structural resistance to earthquake loads, as well as identify important components that require special attention to stability. The analysis results show the presence of horizontal irregularities type 2 on the roof floor due to changes in lateral stiffness, as well as vertical irregularities type 2 (mass) due to the effective mass exceeding 150% of the floor below. Pushover analysis indicates the potential for local collapse in the ground floor columns, but the structure remains stable with roof drifts in the Damage Control category. This indicates that the building remains safe to use after the earthquake.